2021
DOI: 10.3389/fendo.2021.725131
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of β Cell Identity and Dysfunction

Abstract: β cell dysfunction and failure are driving forces of type 2 diabetes mellitus (T2DM) pathogenesis. Investigating the underlying mechanisms of β cell dysfunction may provide novel targets for the development of next generation therapy for T2DM. Epigenetics is the study of gene expression changes that do not involve DNA sequence changes, including DNA methylation, histone modification, and non-coding RNAs. Specific epigenetic signatures at all levels, including DNA methylation, chromatin accessibility, histone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 112 publications
(112 reference statements)
0
12
0
Order By: Relevance
“…Finally, epigenetic signatures may help explain particular functional features of mature and immature beta cells. Both DNA methylation and histone modification are mechanisms by which beta cell identity and function are maintained, through tailoring the expression pattern of beta cell-enriched transcription factors, as well as being regulated by the transcription factors themselves [ 147 , 148 ]. Some relevant examples include DNA methylation through the activity of DNA methyltransferase 3 α (DNMT3A), which has been linked to the repression of beta cell ‘disallowed’ genes, regulated through the mTORC1 component raptor [ 26 ] and through the inhibition of Wnt signalling during SC-islet maturation [ 130 ].…”
Section: Signalling Pathways and Gene Markers Of Beta Cell Maturationmentioning
confidence: 99%
“…Finally, epigenetic signatures may help explain particular functional features of mature and immature beta cells. Both DNA methylation and histone modification are mechanisms by which beta cell identity and function are maintained, through tailoring the expression pattern of beta cell-enriched transcription factors, as well as being regulated by the transcription factors themselves [ 147 , 148 ]. Some relevant examples include DNA methylation through the activity of DNA methyltransferase 3 α (DNMT3A), which has been linked to the repression of beta cell ‘disallowed’ genes, regulated through the mTORC1 component raptor [ 26 ] and through the inhibition of Wnt signalling during SC-islet maturation [ 130 ].…”
Section: Signalling Pathways and Gene Markers Of Beta Cell Maturationmentioning
confidence: 99%
“…By avoiding prolonged exposure to those insults it would be possible to recover mature identity of pre-existing beta cells and their normal functioning. In accordance, advances in experimental and clinical studies have illuminated the substantial role of epigenetic regulatory mechanisms in the development and function of beta cells in physiological conditions, as well as in triggering islet autoimmunity and/or beta cell dysfunction and decline in both T1D and T2D ( 21 , 133 ).…”
Section: Oxidative Stress-related Epigenetic Regulatory Mechanisms As...mentioning
confidence: 99%
“…Growing body of evidence indicate that epigenetic mechanisms such as DNA methylation, chromatin architectural modification and non-coding RNA determine identity of beta cells during embryogenesis and postnatal maturation and maintain their functioning in homeostasis ( 21 ). Diabetes progression and oxidative stress disarrange those epigenetic signatures causing dysfunction and loss of beta cells.…”
Section: Introductionmentioning
confidence: 99%
“…Many epigenetic studies, including the investigation of DNA methylation patterns and accessible chromatin profiles in different tissues, have also contributed to our current knowledge of T2DM [ 172 , 173 ]. One of the most extensive epigenome-wide association studies (EWAS) revealed the CpGs methylation pattern of 52 genes in the blood of European T2DM subjects with the Illumina 450 K methylation array and identified five genes with altered CpG methylation patterns—ABCG1, LOXL2, TXNIP, SLC1A5 and SREBF1—that were significantly associated with the disease [ 174 ].…”
Section: The Potential Role Of Multi-omics and Single Cell-based Tech...mentioning
confidence: 99%